2017
DOI: 10.1111/tri.13005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications of laparoendoscopic single-site donor nephrectomy: a retrospective study

Abstract: The single-port approach has been associated with an unacceptably high rate of umbilical port hernias in large series of patients undergoing single-port cholecystectomy and colectomy and with additional surgical risks thought secondary to technical and ergonomic limitations. A retrospective review of 378 consecutive laparoendoscopic single-site(LESS) donor nephrectomies performed between 04/15/2009 and 04/09/2014 was conducted. Twelve patients (3%) developed an umbilical hernia. Eleven (92%) were female and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In early cases of LESSOP-DN, the incision was made in middle of the umbilicus, but in later cases the incisions were modified to periumbilical incisions, which prevented hernias afterwards. When comparing our results to those of other studies, La Mattina et al reported that the most common complication in LESS-DN was an umbilical hernia, which resulted in 1.9% postoperative hernia operations [32]. Serrano et al reported a 4% rate of incisional hernia in HALDN [33].…”
Section: Discussionsupporting
confidence: 60%
“…In early cases of LESSOP-DN, the incision was made in middle of the umbilicus, but in later cases the incisions were modified to periumbilical incisions, which prevented hernias afterwards. When comparing our results to those of other studies, La Mattina et al reported that the most common complication in LESS-DN was an umbilical hernia, which resulted in 1.9% postoperative hernia operations [32]. Serrano et al reported a 4% rate of incisional hernia in HALDN [33].…”
Section: Discussionsupporting
confidence: 60%
“…We sometimes experience adhesional hernias after abdominal surgery, however, an internal hernia after RLN is rare. We searched PubMed for reports of an internal hernia after RLN, and only 17 cases have been reported in literature including our case (Table 1) [1,2,5,[10], [11], [12], [13], [14], [15], [16], [17], [18], [19]]. Radical nephrectomy for cancer and donor nephrectomy comprised of seven cases each.…”
Section: Discussionmentioning
confidence: 99%
“…Nonclosure of the mesenteric defect may cause internal herniation, which in turn can cause intestinal obstruction [ 5 9 ]. However, the occurrence of such obstruction has not been well documented, and closure of mesenteric defects remains in debate [ 10 12 ]. In the past, there were case reports on the issues regarding repair of the mesenteric defect of right colectomy as the standard procedure [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%